2022
DOI: 10.1371/journal.pone.0271179
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum total bilirubin levels with progressive renal decline and end-stage kidney disease: 10-year observational cohort study in Japanese patients with diabetes

Abstract: Objective Previous reports have demonstrated the association of serum bilirubin levels with the progression of diabetic nephropathy. The objective of this study is to assess the association of basal bilirubin levels with progressive renal decline (PRD) and end-stage kidney disease (ESKD). Methods A total of 298 patients with diabetes who visited Kyushu University Hospital (Japan) were recruited and followed up for 10 years. PRD was defined as a negative change in estimated glomerular filtration ratio (eGFR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…( 14 ) showed that the serum total bilirubin level was significantly lower in DN patients compared with non-DN patients and was significantly associated with an increased risk of DN patients. A 10-year observational cohort study in Japanese patients with diabetes was to evaluate the association of baseline serum TBIL levels with progression of DN and found that serum TBIL levels were negatively associated with PRD in diabetic nephropathy and its cut-off point was 0.5 mg/dL ( 8 ). Liu M et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 14 ) showed that the serum total bilirubin level was significantly lower in DN patients compared with non-DN patients and was significantly associated with an increased risk of DN patients. A 10-year observational cohort study in Japanese patients with diabetes was to evaluate the association of baseline serum TBIL levels with progression of DN and found that serum TBIL levels were negatively associated with PRD in diabetic nephropathy and its cut-off point was 0.5 mg/dL ( 8 ). Liu M et al.…”
Section: Discussionmentioning
confidence: 99%
“…Eto et al. ( 8 ) further validated the clinical utility of serum TBIL (≤0.5 mg/dL) in predicting and identifying high risk of ESRD in DKD patients. These findings are rooted in the anti-inflammatory and anti-oxidative stress properties of bilirubin, which were examined in relation to serum bilirubin levels at a certain time point to delay DKD progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the past twenty years, a series of cross-sectional studies have consistently suggested an association between high STB levels and a reduced risk of DKD in patients with diabetes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Concurrently, animal studies have been conducted to explore the mechanism whereby STB confers protection against DKD (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Bilirubin, as the final product of heme catabolism, includes total bilirubin (TBIL), indirect bilirubin (IBIL), and direct bilirubin (DBIL). 5 Recent studies have shown that bilirubin might be a possible candidate biomarker for DM 6 and diabetic complications [7][8][9] due to its potent antioxidant and anti-inflammatory properties. To date, there are few studies investigating the relationship between serum TBIL and diabetic vascular complications.…”
Section: Introductionmentioning
confidence: 99%